Effect of electrolyte-plasma surface hardening on structure wheel steel 2 - Rakhadilov, B.K.; Tabiyeva, Y.Y.; Uazyrkhanova, G.K.; Zhurerova, L.G.; Popova, N.A. (KSU Publ., 2020)
This paper examines the influence of electrolyte-plasma surface hardening on the structure and microhardness of wheel steel mark 2. In the work electrolyte-plasma surface hardening was carried out in an electrolyte made from an aqueous solution 10 % carbamide (NH2)2CO 20 % sodium carbonate Na2CO3. The processing time was 2 seconds, Tmax = 850–900 ºC; U= 320V; I=40A. According to the results of the scanning transmission electron microscopy, the electrolyte-plasma surface hardening caused a change in the morphological constituents of mark 2 steel. In the initial state, the matrix of steel is a α-phase, the morphological components of which are fragmented ferrite, unfragmented ferrite and pearlite. After electrolytic-plasma surface hardening, a batch, high-temperature plate and low-temperature plate martensit is formed on the surface of the sample. Investigations have been carried out on microhardness determination on cross-section of wheel steel samples after quenching in aqueous solution of electrolyte. It is found that after electrolytic-plasma surface hardening, the microhardening values of this hardened surface layer increased ~ 3 times compared to the steel matrix, and the thickness of the hardened layer is 1000–1500 microns.
Электролитті-плазмалық беттік шынықтырудың 2 маркалы дөңгелек болаттың құрылымына əсері
Влияние электролитно-плазменной поверхностной закалки на структуру колесной стали марки 2
Keywords: electrolytic-plasma surface hardening; wheel steel; transmission electron microscopy; fine structure; microhardness; morphology; martensite